The Mentoring of Senior High School Physics Teachers In Improving Students' Scientific Questions Ability - nurul wati; Evendi Evendi; Yusrizal Yusrizal (Asian Journal of Science Education, 2020)
The ability of students to ask questions is one of the obstacles faced by teachers when teaching. Most students do not want to ask questions when the teacher gives the chance to ask questions. The low ability of students to ask questions was also influenced by the ability of teachers to raise the enthusiasm of students to ask questions also experienced by physics teachers in Aceh Tengah. Therefore, it is necessary to increase teacher professionalism in these activities. The purpose of this activity is to provide support to physics teachers on how to improve students' scientific questioning skills in physics lessons at SMA Aceh Tengah District. The target of Community Service activities in 2020, is the core teachers in the field of Physics in Aceh Tengah Regency, totaling 10 people. Implementation of assistance uses the Question Web-Based Learning (QWBL) learning model or the questions based learning model. Assistance material is the development of student worksheets based on questions or called the student activity question web worksheets (SQWS). SQWS is a question sheet that can link one question with other questions about the material being studied. The teacher's ability to improve students' scientific questioning skills in learning physics is measured using the Scientific Asking Skills Assessment Sheet (SASAS) or scientific questioning skills test assessment sheet. The results of the mentoring show that the teacher's ability to ask questions before going mentoring is in the average scientific category and less scientific, whereas after mentoring the average ability of the teacher to ask is in the scientific category and very scientific. This shows that the mentoring activity very helped physics teachers to improve students' scientific questioning skills at SMA Aceh Tengah district.